2019
DOI: 10.3389/fmicb.2019.01987
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Nuclear Number and Size in Vegetative Hyphae of the Edible Mushroom Lentinula edodes

Abstract: In basidiomycete fungi, the number of nuclei and their ploidy level per nucleus can vary tremendously among species; however, within species, nuclear number and ploidy levels are traditionally considered fixed in their vegetative hyphae. In the edible mushroom Lentinula edodes, the hyphae are classified as either monokaryotic or dikaryotic, with each monokaryotic hyphal cell containing one haploid nucleus, and each dikaryotic hyphal cell containing two haploid nuclei. The dikaryotic hyphae are the results of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…Our findings indicate that even though clamp connections can be used to separate heterokaryons from homokaryons, the nuclear condition of hyphal cells is not always a key characteristic that can be used to distinguish between homokaryotic hyphae and heterokaryotic hyphae. Additionally, our results were similar to those of a study on Lentinula edodes, which showed that around 52% of the binucleate heterokaryotic hyphal cells and around 41% of the multinucleate homokaryotic hyphal cells were present in the initial stage of culture (Gao et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…Our findings indicate that even though clamp connections can be used to separate heterokaryons from homokaryons, the nuclear condition of hyphal cells is not always a key characteristic that can be used to distinguish between homokaryotic hyphae and heterokaryotic hyphae. Additionally, our results were similar to those of a study on Lentinula edodes, which showed that around 52% of the binucleate heterokaryotic hyphal cells and around 41% of the multinucleate homokaryotic hyphal cells were present in the initial stage of culture (Gao et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…From a life cycle perspective, L. edodes is a tetrapolar basidiomycete, and most of its young dikaryotic hyphal cells contain two haploid nuclei each and share a single cytoplasm without undergoing nuclear fusion [12]. Only dikaryon can form primordia and develop into fruiting bodies in this and many other mushroom species.…”
Section: Introductionmentioning
confidence: 99%
“…This observation is also consistent with the low growth rate of GT at an EPL concentration of 1 mg/ml. In comparison, part of the nuclei fragmented in the remaining three fungal stains upon EPL treatment (Gao et al, 2019 ), and some of them remain unchanged. These results could explain why RP and IL were less sensitive to EPL treatment at 1 mg/ml.…”
Section: Resultsmentioning
confidence: 99%